2009
DOI: 10.1007/s00726-009-0446-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of muscle and plasma amino acids in healthy children

Abstract: The aim of the study was to explore if changes in muscle and plasma amino acid concentrations developed during growth and differed from levels seen in adults. The gradient and concentrations of free amino acids in muscle and plasma were investigated in relation to age in metabolic healthy children. Plasma and specimens from the abdominal muscle were obtained during elective surgery. The children were grouped into three groups (group 1: < 1 year, n = 8; group 2: 1-4 years, n = 13 and group 3: 5-15 years, n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…With regard to ornithine, in our subjects, the levels of this amino acid were about 50% higher compared to those previously described in healthy children of a similar age [23,24]. A weak increase in plasma ornithine between six and sixteen years of age was reported by Lepage et al [23], which was confirmed in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With regard to ornithine, in our subjects, the levels of this amino acid were about 50% higher compared to those previously described in healthy children of a similar age [23,24]. A weak increase in plasma ornithine between six and sixteen years of age was reported by Lepage et al [23], which was confirmed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, an increase of homoarginine with age in our healthy children and adolescents might result from gradual maturation of the pathways controlling homoarginine metabolism. An age-dependency of plasma concentrations of several amino acids had previously been described in a healthy pediatric population [23,24], nevertheless, homoarginine was not measured in those studies. Additionally, in contrast to homoarginine, plasma arginine was independent of age in our study group, in agreement with a previous report on 54 healthy children with a mean age of 11.9 ± 4.6 years [25].…”
Section: Discussionmentioning
confidence: 99%
“…As observed previously, plasma methionine, tHcy and cysteine increased with age [33], [34]. We observed that tCys in both genders and methionine in girls reached a plateau around puberty.…”
Section: Discussionsupporting
confidence: 87%
“…Healthy neonates show similar plasma glutamine concentrations as adults, although the scatter is larger (Hammarqvist et al 2010;Oladipo et al 2011). Critically ill neonates on the other hand show low plasma glutamine concentrations (Becker et al 2000;Oladipo et al 2011).…”
Section: Introductionmentioning
confidence: 91%